School engagement profiles in Chilean secondary students - de Toro, Ximena; Saracostti, Mahia; Lara, Laura; Miranda, Horacio; Miranda-Zapata, Edgardo (Frontiers in Psychology, 2023)
School engagement is considered a key variable in promoting educational trajectories. Previous research shows that maintaining high levels of school engagement is fundamental, given its association with multiple academic results and lower-risk behaviors. This article aims to show how school engagement profiles (based on the behavioral, affective, and cognitive subdimensions) relate to academic achievement (math and language), contextual factors (family, teachers, and peer support), and gender. This study involved 527 students enrolled in the 1st year of secondary education in public schools in Chile. All students came from vulnerable schools. Our study used cluster analysis to identify students’ profiles. We identified the existence of three different profiles of school engagement (high, medium, and low) considering the three subdimensions of school engagement (behavioral, affective and cognitive). Secondly, ANOVA analysis showed differences in language and math academic achievement scores between the profiles, where higher engagement students showed higher academic performance in language and math. These findings are consistent with previous studies showing that contextual factors strongly influence school engagement and better behavioral engagement in female than male students. It will discuss the pertinence of person-centered approaches focusing on combinations of variables within students rather than taking each variable as the focal point when analyzing goals. These techniques are a favorable methodological alternative to investigate why some students have better results than others instead of just ranking students by their performance. It will conclude with some future lines of research and practical implications.